Feu la D.C.D. L'arrêt Miller et la peine de mort - Brun, Henri (Les Cahiers de droit, 1977)
The Miller case, decided by the Supreme Court of Canada on October 5, 1976, puts the death penalty under the light of the Canadian Bill of Rights which formulates the right to life and the right to protection against cruel and unusual treatment or punishment. The following comment on the case relates to the interpretation given specific clauses of the Bill of Rights by the Court on that occasion. But it stresses especially the law that flows from the case about the compelling weight of the Bill of Rights over acts of Parliament enacted after the Bill came into force. In Miller, the Supreme Court expressed itself on the subject for the first time.